HER-2 Neu gene: A valuable therapeutic target in metastatic mucoepidermoid carcinoma. (October 2021) - Mohammed, Turab; Mangeshkar, Shaunak; Desai, Aakash; Hegde, Upendra
Introduction: Salivary gland neoplasms (SGNs) respond poorly to the traditional chemotherapy agents limiting the availability of systemic treatment options in the metastatic setting. The recent identification of actionable molecular targets in SGNs has led to the evaluation of targeted therapies in non-approved advanced SGNs. Case Report: We present the case of an elderly male with HER-2 Neu overexpressing metastatic mucoepidermoid carcinoma (MEC) who demonstrated a prompt and sustained disease response to targeted therapies directed against HER-2 Neu with long survival interrupted by hepatoxicity to Trastuzumab emtansine (TDM-1) treatment. Management and Outcome: The patient was started on Trastuzumab and Pertuzumab on a clinical trial and resulted in an objective improvement sustained over 3 years. Following the disease progression, TDM-1 was started with a response until the patient developed severe hepatotoxicity as an adverse effect of TDM-1 therapy resulting in its discontinuation. Close follow-up post-treatment-discontinuation demonstrated continued clinical improvement until 6 months, when the patient developed brain metastasis. He passed away a few months later in hospice care. Discussion: The metastatic MEC in our patient overexpressed HER-2 Neu. Owing to Trastuzumab and Pertuzumab response, Trastuzumab emtansine (TDM-1) was initiated on a compassionate basis which further extended the survival but had to be terminated owing to adverse effects. Given the paucity of data on targeted therapies in the treatment of metastatic SGNs and the safety, tolerability, and efficacy of TDM-1 therapy among the elderly, further studies are warranted to answer these important questions and to identify eligible patients for this novel treatment option.